Emerging 0D, 1D, 2D, and 3D nanostructures for efficient point-of-care biosensing - Byakodi, Manisha; Shrikrishna, Narlawar Sagar; Sharma, Riya; Bhansali, Shekhar; Mishra, Yogendra; Kaushik, Ajeet; Gandhi, Sonu (Biosensors and bioelectronics. X, 2022)
The recent COVID-19 infection outbreak has raised the demand for rapid, highly sensitive POC biosensing technology for intelligent health and wellness. In this direction, efforts are being made to explore high-performance nano-systems for developing novel sensing technologies capable of functioning at point-of-care (POC) applications for quick diagnosis, data acquisition, and disease management. A combination of nanostructures [i.e., 0D (nanoparticles & quantum dots), 1D (nanorods, nanofibers, nanopillars, & nanowires), 2D (nanosheets, nanoplates, nanopores) & 3D nanomaterials (nanocomposites and complex hierarchical structures)], biosensing prototype, and micro-electronics makes biosensing suitable for early diagnosis, detection & prevention of life-threatening diseases. However, a knowledge gap associated with the potential of 0D, 1D, 2D, and 3D nanostructures for the design and development of efficient POC sensing is yet to be explored carefully and critically. With this focus, this review highlights the latest engineered 0D, 1D, 2D, and 3D nanomaterials for developing next-generation miniaturized, portable POC biosensors development to achieve high sensitivity with potential integration with the internet of medical things (IoMT, for miniaturization and data collection, security, and sharing), artificial intelligence (AI, for desired analytics), etc. for better diagnosis and disease management at the personalized level. •Emerging novel nanomaterial's potential use in Point-of-care (POC) biosensing devices is reviewed.•Different dimensions nanomaterials integration for the development of POC biosensors for enhanced performance are explained.•The advantages of nanomaterials utility in POC devices for miniaturizing and for low Limit of detection have been mentioned.•Integration of AI and IoMT in biosensors for improved disease management is highlighted.•The challenges, approaches, and future perspectives of nanomaterials-based biosensors are discussed.